The use of dolomite to overcome grounding resistance in acidic swamp land - Dian Eka Putra; Muhammad Irfan Jambak; Zainuddin Nawawi (Universitas Ahmad Dahlan, 2025)
This research addresses the effectiveness of grounding systems in acidic swampland, which poses a challenge in protecting people and electrical equipment from the risk of electric shock. The increasing use of swampland for electrical installations necessitates a solution to reduce the high grounding resistance resulting from poor soil resistivity values. This study proposes using dolomite as an admixture to improve soil conductivity and lower grounding resistance. Experimental methods were conducted by embedding rod electrodes of various materials in dolomite-mixed media with varying compositions. The results showed that adding dolomite significantly decreased the grounding resistance, although there were inconsistencies in the test results; on average, the decrease in resistance reached 25%. Galvanized electrodes proved to be the most effective in this system. These findings provide new insights in the field of grounding systems and offer practical solutions that are environmentally friendly and sustainable. This research is expected to be an important reference for developing more innovative and effective grounding system techniques in the future.